Productive, reproductive and adaptative qualities of holshtian breed cows of different lines - Підпала, Т. В.; Крамаренко, О. С.; Зайцев, Є. М. (Scientific Progress & Innovations, 2018)
The article presents the results of the research work on the development of breeding features in cows of different lines of Holstein breed. It was established that cows of all lines are characterized by a high level of milk indicators. In the process of adaptation imported cows of German breeding showed a sufficiently high level of milk and fat in milk. Compared to them, the descendants of the next generation were distinguished by higher tastes, but were losing them in the fat content of milk, with the exception of Starbuck's and Chief's lines. Among the cows of Holstein breed of Ukrainian selection, preference for milk yield was found for Starbuck, Marshall and Chifa animals.